Assessing the effects of the cone force ratio on the performance of hydrocyclones - Synopsis - D. Lusinga (The Southern African Institute of Mining and Metallurgy, 2009)
Hydrocyclones are a common feature in almost all mining operations in the world, serving mainly as classifiers. Some of their advantages include low capital costs, low space requirements and their ability to reduce residence time in closed circuit grinding processes. Although an extensive body of literature exists for hydrocyclones, these devices are still inherently inefficient, and more research is currently being undertaken, particularly in the field of modelling. In the vast body of hydrocyclone literature published so far, there has been little or no effort devoted to analysing the effect of the cone force ratio on the performance of hydrocyclones. The cone force ratio is defined as the ratio of the spigot to the vortex finder diameter (Shah, 2005). In this study a total of 44 tests was carried out in a custom-built rig at the University of Cape Town. These tests were aimed at evaluating the effect of the cone force ratio on the performance of as mall diameter hydrocyclone. The cut size and water split were used as the criterion for evaluating the performance of the hydrocyclone. Results from the tests showed that the cut size decreased with an increase in the cone force ratio. The cut size also appeared to decrease as the calculated locus of zero vertical velocity (LZVV) shifted inwards. The water recovery to the underflow appeared to increase with an increase in the cone force ratio. The effect on the cut size of adjusting the cone force ratio was found to be higher for a coarser feed than it was for a finer feed.